2002
DOI: 10.1080/00207590143000289
|View full text |Cite
|
Sign up to set email alerts
|

Parents' structuring of children's daily lives in relation to the quality and stability of children's friendships

Abstract: This study focused on the implications of parents' structuring of their children's home lives for the friendships of their children. Participants were 224 elementary-school children (108 girls and 116 boys) from four grade levels in two schools in Aixen-Provence, France. Most of the families were of middle or high socio-economic status. The participating children were seen twice during the same school year in order to assess the stability of their friendship choices and the quality of their friendships. We use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
5
0
2
Order By: Relevance
“…The FQS is a self-reported questionnaire that assesses the quality of children's relationship with their best friend on a 5-point Likert scale ranging from 1 ¼ ''not true'' to 5 ¼ ''really true''. The 22 items of the questionnaire can be aggregated on two scales: Warmth and Conflict (AllesJardel, Fourdrinier, Roux, & Schneider, 2002). The FQS has been previously used with Italian children of similar age and has showed good psychometric properties (Lecce, Pagnin, & Pinto, 2009).…”
Section: Measures and Proceduresmentioning
confidence: 99%
“…The FQS is a self-reported questionnaire that assesses the quality of children's relationship with their best friend on a 5-point Likert scale ranging from 1 ¼ ''not true'' to 5 ¼ ''really true''. The 22 items of the questionnaire can be aggregated on two scales: Warmth and Conflict (AllesJardel, Fourdrinier, Roux, & Schneider, 2002). The FQS has been previously used with Italian children of similar age and has showed good psychometric properties (Lecce, Pagnin, & Pinto, 2009).…”
Section: Measures and Proceduresmentioning
confidence: 99%
“…The authors originally identified 5 dimensions: Companionship (e.g., ''We spend our time together''); Conflict (e.g., ''We can argue a lot/my friend and I disagree''); Help (e.g., ''My friend helps me if I need it''); Closeness (e.g., ''I feel happy when I am with my friend''); and Security measured with two sets of items, one regarding transcending problems (e.g., ''If my friend and I have a fight or argument, we can say 'I am sorry' and everything will be all right''), and the other regarding the reliability of the alliance (e.g., ''If I have a problem at school or at home I can talk to my friend about it''). However, a review of the recent literature provides clear evidence for a 2 factors solution: Affection and Conflict (Alles-Jardel et al, 2002;Lecce, Primi, Pagnin, & Menzione, 2006;Weimer et al, 2004). Internal consistency of these two factors was found to be good in the present study (Cronbach's alpha Conflict ¼ .76; Cronbach's alpha Affection ¼ .70).…”
Section: Methodsmentioning
confidence: 44%
“…In other words, it could be possible that preadolescents have a more widely shared knowledge of their friendship because friendship during preadolescence is particularly intimate and close (Bukowski, Newcomb, & Hartup, 1996). However, although this could well be the case, other studies reported a high and significant correlation between ratings by members of a best-friends' dyad both on positive and on negative dimensions during childhood as well as during adolescence (Alles-Jardel, Fourdrinier, Roux, & Schneider, 2002;Schneider, Fonzi, Tani, & Tomada, 1997).…”
Section: Congruence In Friend Dyadsmentioning
confidence: 93%
“…Since establishing and maintaining healthy friendship relationships is one of the important factors in adolescent development, related instruments should be developed and adapted. As a result, the Friendship Qualities Scale (FQS), developed by Bukowski et al (1994) and adapted for use both with French adolescents (Alles-Jardel, Fourdrinier, Roux, & Schneider, 2002) and with Italian adolescents (Ponti, Guarnieri, Smorti, & Tani, 2010), has been chosen for adaptation and use in Turkey with the present study intending to be an adaptation study of this particular scale.…”
mentioning
confidence: 99%